PENGARUH WORK-LIFE BALANCE DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI PADA PT. X - Rosyadah, Hikmah; Ardyanfitri, Helmina (Growth, 2026)
This study is entitled “The Effect of Work-Life Balance and Work Environment on Employee Performance with Work Motivation as a Mediating Variable at PT X.” The purpose of this study was to analyze the effect of work-life balance and work environment on employee performance with work motivation as a mediating variable. This research used a quantitative method with a causal approach by collecting primary data through surveys and questionnaires distributed to employees of the Corporate Secretary Department at PT X. Data were analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS) version 4.1.1.7, with a sample of 65 employees selected using proportionate stratified random sampling. The results showed that work-life balance and work environment did not significantly affect employee performance, but both had a positive and significant effect on work motivation. Furthermore, work motivation had a positive and significant effect on employee performance and significantly mediated the relationship between work-life balance, work environment, and employee performance. These findings indicate that improving employee performance requires strengthening work motivation alongside improvements in work-life balance and work environment, contributing to human resource management literature and providing practical implications for organizations and future research.